PENGEMBANGAN UMKM MELALUI INOVASI PENGOLAHAN IKAN ASAP MENJADI ABON DI DESA TEDUNAN KEDUNG JEPARA - Nadhiroh, Fitri Ainun; Sutriyani, Wulan (Jurnal Pengabdian kepada Masyarakat Khaira Ummah, 2023)
Real Work Lecture (KKN) is a form of community service implementation as one of the pillars of the Tri Dharma of Higher Education which must be followed by students where students collaborate with lecturers to apply knowledge and competencies according to their scientific fields to the community. The purpose of this community service is to help solve problems in the community, precisely in the business / industrial world through innovations in processing smoked fish into shredded. The implementation method in this community service is socialization, education, and community training in order to achieve the results of planning and developing innovations in processing smoked fish into shredded. The results of this community service are as follows. (1) Micro, Small and Medium Enterprises (MSMEs) are an integral part of the people's economy that has a strategic position to realize an increasingly balanced, developing and equitable national economic system. (2) Smoked fish is fish preserved through fumigation. Innovating the processing of smoked fish into shredded fish which is processed through the boiling stage, frying and pressing or oil separation, but previously the ingredients that have passed the shredding stage with a small size which aims to facilitate the process of roasting fish and seasonings (3) Making Shredded Smoked Fish Product Labels, (4) Development of Shredded Smoked Fish Product Packaging and (5) Development of Promotion Systems and Distribution of Shredded Smoked Fish Products.